2009
DOI: 10.3126/eco.v15i0.1940
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Behaviour of the Himalayan Honeybee (<i>Apis cerana</i> F.) on Flowers of <i>Fagopyrum esculentum</i> M. and its Impact on Grain Quality and Yield

Abstract: This paper presents the findings of two studies - one conducted on foraging behaviour of Himalayan honeybee (Apis cerana F.) on flowering buckwheat (Fagopyrum esculentum Moench) in November 2001 to 2002 and another on its impact on the grain quality and yield increment of this crop conducted during 2000-2002 under different pollination treatments at Kirtipur, Kathmandu valley. Apis cerana bees started their foraging activities early in the morning (06.14 ± 0.004) and ceased late in the evening (17.28 ± 0.011).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In an apple orchard in Northern India, A. cerana indica foraged earlier in the day compared to A. mellifera , being most active between 9 a.m. and 11.30 a.m. when temperatures were between 15.5 and 21 °C, compared to A. mellifera , which were most active between 11 a.m. and 1:30 p.m. at temperatures between 21–25 °C (Verma, 1995 in [ 25 , 38 ]). In Kathmandu, Nepal, there were two peak foraging times per day, which corresponded with temperatures of 20–21 °C [ 39 ].…”
Section: Ecology and Behaviourmentioning
confidence: 99%
“…In an apple orchard in Northern India, A. cerana indica foraged earlier in the day compared to A. mellifera , being most active between 9 a.m. and 11.30 a.m. when temperatures were between 15.5 and 21 °C, compared to A. mellifera , which were most active between 11 a.m. and 1:30 p.m. at temperatures between 21–25 °C (Verma, 1995 in [ 25 , 38 ]). In Kathmandu, Nepal, there were two peak foraging times per day, which corresponded with temperatures of 20–21 °C [ 39 ].…”
Section: Ecology and Behaviourmentioning
confidence: 99%
“…A case study of A. cerana pollination of common buckwheat found that this bee began its foraging activities early in the morning and ceased late in the evening, a period of approximately 10 h/day. Pollination by A. cerana increased seed mass and the conversion of ovaries into fruits, increasing yield and fruit size substantially (Singh, 2009). Although China is one of the biggest buckwheat producers internationally, the national buckwheat crop of China decreased from 2.5 million ha in 1961 to 0.74 million in 2011 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled data revealed that significantly (p<0.01) highest number of pollinators were observed during 9 to 10 am of the day (2.38±0.42 pollinators), followed by 12 noon to 1 pm (1.99±0.59 pollinators) and 3 pm to 4 pm (1.30±0.45 pollinators) ( Figure 2). Singh et al (2008) reported morning hour (8:30-9:30 am) as the peak foraging period in buckwheat followed by afternoon period for the Himalayan honeybee, Apis cerana F., however, the authors argued both periods as very important from pollination perspectives. Also, the high-altitude buckwheat cultivation areas are generally characterized by good sunshine during the morning, and a windy cold climate 120 | P a g e after 12 pm.…”
Section: Pollinators Population Visit In Different Buckwheat Genotypementioning
confidence: 98%
“…The total foraging hours of the pollinator varied from 8.45 to 9.45 hours. Singh et al (2008) reported the 10-hour duration of foraging activity in buckwheat crop observed at Kirtipur, Kathmandu, Nepal during November month of the study. Aryal et al (2016) and Campbell et al (2016) found a huge number of pollinating insects were attracted by buckwheat flowers, along with a huge diversity of beneficial predators and parasitoids.…”
Section: Pollinators Population Visit In Different Buckwheat Genotypementioning
confidence: 99%